The Effect of Perceptions, Services and System Security on Customer Interest in Using Mobile Banking Applications - Syahruddin Syahruddin; Syamsul Alam; Dewi Pratiwi Indriasari (International Journal of Artificial Intelligence Research, 2022)
The objectives of this study were 1) to determine and analyze the effect of perception on customer interest in making repeat transactions on mobile banking applications, 2) to determine and analyze the effect of services on customer interest in making repeat transactions on mobile banking applications, and 3) to determine and analyze the effect of system security on customer interest in making repeat transactions on mobile banking applications. The research approach is an explanatory causal approach. The analysis method used in this research is the Multiple Regression analysis method. The results showed that 1) Perception has a positive and significant effect on customer interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea, this shows that the better the customer's perception, the higher the customer's interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea, 2) Service has a positive and significant effect on customer interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea, this shows that the better the service provided by employees, the higher the customer's interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea, and 3) System security has a positive and significant effect on customer interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea, this shows that the better the security of the BRImo system, the higher the customer's interest in making repeat transactions on mobile banking applications at BRI Kanca Tamalanrea.